2007
DOI: 10.1002/anie.200701626
|View full text |Cite
|
Sign up to set email alerts
|

A Titanium Disilicide Derived Semiconducting Catalyst for Water Splitting under Solar Radiation—Reversible Storage of Oxygen and Hydrogen

Abstract: Dedicated to Professor Kurt Schaffner on the occasion of his 75th birthdayHydrogen and oxygen evolution from water using semiconductors and light is an important issue in the exploitation of solar radiation as a sustainable energy. [1,2] However, a major drawback of most of the research in this field relates to the fact that appropriate semiconductors either are not readily accessible, absorb solar radiation inefficiently, [3][4][5][6][7][8] or produce hydrogen in a sacrificial manner only (i.e. the catalyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 22 publications
1
81
0
Order By: Relevance
“…Therefore, to a solution of bmpphenO 2 in dry methanol, phen(NH 2 ) 2 was added in portions to avoid a possible self-condensation of phen(NH 2 ) 2 to tpphz. Finally, the complexation of the obtained ligand bmptpphz with [(tbbpy) 2 RuCl 2 ] (tbbpy = 4,4′-di-tert-butyl-2,2′- bipyridine) was carried out in ethanol-water at reflux to obtain the brownish target molecule Ru(bmptpphz) in 78% yield. In comparison, the complexation of the unsubstituted tpphz with [(tbbpy) 2 RuCl 2 ] has to be performed at 200°C in refluxing ethylene glycol with a three-fold excess of the ligand to guarantee a sufficient solvation of tpphz and to avoid a complexation of the ruthenium moiety on both coordination sites.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to a solution of bmpphenO 2 in dry methanol, phen(NH 2 ) 2 was added in portions to avoid a possible self-condensation of phen(NH 2 ) 2 to tpphz. Finally, the complexation of the obtained ligand bmptpphz with [(tbbpy) 2 RuCl 2 ] (tbbpy = 4,4′-di-tert-butyl-2,2′- bipyridine) was carried out in ethanol-water at reflux to obtain the brownish target molecule Ru(bmptpphz) in 78% yield. In comparison, the complexation of the unsubstituted tpphz with [(tbbpy) 2 RuCl 2 ] has to be performed at 200°C in refluxing ethylene glycol with a three-fold excess of the ligand to guarantee a sufficient solvation of tpphz and to avoid a complexation of the ruthenium moiety on both coordination sites.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The ligand bmptpphz (0.49 g, 0.82 mmol) was suspended in ethanol-water (100 ml/100 ml) and heated to reflux. Afterwards [(tbbpy) 2 RuCl 2 ] (0.60 g, 0.85 mmol) in ethanol-water (50 ml/50 ml) was added during 1 hour. The orange-brown suspension was refluxed for 18 hours more and subsequently filtered while hot to remove unreacted ligand.…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating Pt or RuO 2 nanoparticles on the surface as suggested by Shangguan [14] could be a method of increasing the density of such sites. Ritterskamp et al [58] reported the use of TiSi 2 as a catalyst for photocatalytic water splitting based on its broadband absorption characteristics (band gap range is 3.4-1.5 eV). TiSi 2 is however unstable in water due to oxide formation.…”
Section: Tio 2 and Its Nanostructures For Photoelectrochemical Applicmentioning
confidence: 99%
“…Titanium silicides are potential candidates for field emission devices due to their relative low resistivity (10-28μΩ cm), high thermal stability, and low work function. Ritterskamp et al reported that the light-absorption characteristics in UV-visible region (ca.360∼800nm) of TiSi 2 are ideal for solar applications and have a good photocatalytic activity of splitting water into hydrogen [3]. There are a lot of the reports on the shock-induced chemical reaction for Ti-Si concerning to the role of morphologies of the powder mixtures, shock energy and the presence of oxygen [4,5].…”
Section: Introductionmentioning
confidence: 99%